The effect of tropical cyclones on economic activities: Micro level evidence from Mexico for secondary and tertiary activities - Miriam Juarez-Torres; Jonathan Puigvert (Banco de México, 2021)
This paper explores the effects of tropical cyclones on the economic activity of establishments in the manufacturing and service sectors in Mexico. The analysis relies on panel data that combines establishment-level economic activity with municipal-level exposure to tropical cyclones on a monthly basis to estimate an augmented distributed lag model. Results show that, after a tropical cyclone, the average manufacturing establishment experiences a short-term and small negative effect on production growth. For establishments in the service sector, the effect is small and negative on revenue growth, while positive, higher in magnitude, and more persistent on growth of operative expenditures. The disaggregated data allows for the analysis of the heterogeneity of the effects between manufacturing and services sectors.
Keywords: Q54; Q51; L60; O12; O14; 330; Tropical cyclones; Establishments; Economic impact; Maximum sustained wind exposure